Investigation of some biochemical parameters of wild and culturedMyrtus communisL. fruits subjected to different conservation methods - Cakmak, Meltem; Bakar, Busra; Ozer, Dursun; Geckil, Hikmet; Karatas, Fikret; Saydam, Sinan (Springer, 2021)
In this study, wild and cultivated whiteMyrtus communisL. (myrtle) fruits were investigated for their vitamin levels (A, B, C and E), carotenes (lycopene, beta-carotene), functional peptides (glutathione, ghrelin), oxidative stress markers (GSSG and MDA), total phenolic and flavonoid substances, antioxidant capacity (DPPH, TEAC) and essential elements (Se, Zn, Fe, Cu and Mn). The results showed that both myrtle fruits can be considered as the good source of vitamins, antioxidants and elements. The preservation (sun or microwave-drying) methods for this seasonal fruit caused a significant (p < 0.05) decrease in their biochemical and bio-pharmacological content compared to fresh or frozen fruits. On the contrary, preservation resulted a significant increase in GSSG and MDA levels. The amounts of Se, Zn, Fe, Cu and Mn in wild myrtle fruit were found as 0.58, 205, 228.0, 37.22 and 24.3 mu g/g dw, respectively.
Keywords: Myrtus communisL; Preservation; Vitamins; Phenolic substance; Antioxidant capacity